Formation of the sale price: a study with family poultry farmers inserted in PAF - Alisson Lino de Lima; Tatiana Frey Biehl Brandão (Universidade Estadual de Alagoas, 2021)
Rural accounting should not only be used for tax purposes, as this is also a management tool. Thus, the work aims to investigate how the sale price of eggs from free-range chickens is determined by producers from Santana do Ipanema -AL inserted in the Family Poultry Program (PAF). Methodologically, the research has a quantitative and qualitative approach. Among the procedures adopted, a search for information was carried out at the Cooperative of poultry farmers and at the Secretariat of Agriculture of Santana do Ipanema. In a second moment, 44 semi-structured interviews with poultry farmers active in the PAF were carried out. It was found that the studied family poultry farmers affirm that they do not have knowledge about accounting and about any method of measuring production costs, thus they do not use accounting and cost information to assist in the formation of the selling price of their products. Therefore, the sales price charged is determined by the poultry farmers' cooperative, which is based on the cost survey carried out by the technical assistance offered to the cooperative members.